Carbonic anhydrase activity and its role in membrane H+-equivalent transport in mammalian ventricular myocytes - Villafuerte, F (2007)
Carbonic anhydrases (CAs) are fundamental and ubiquitous enzymes that catalyse the reversible hydration of CO2 to form HCO3- and H+ ions. Evidence derived from heterologous expression systems has led to the proposal of a novel role for CA in intracellular pH regulation, where its physical and functional coupling to membrane H+ -equivalent transport proteins appears to enhance their activity. It has yet to be established whether such a functional association occurs naturally in wild-type cells. Additional evidence on CA activity in-vitro, has also suggested that certain CA isoforms are regulated by physiological changes of pH, an effect that may then affect their ability to enhance H+ -equivalent transport. No information, however, exists on the pH sensitivity of CA in intact cells. Finally, pharmacological inhibition of CA activity has been reported previously for various compounds, in addition to those designed specifically as CA inhibitors. It is possible that some compounds, currently used to inhibit membrane H+ transport, may also target CA. The present work has examined functional aspects of CA activity in ventricular myocytes isolated enzymically from rat heart, focusing on the potential role of C A in controlling sarcolemmal Na+/H+ exchange (NHE) and sarcolemmal Na+-HCO3- cotransport (NEC). NHE and NEC activity were estimated from the rate of recovery of intracellular pH (pHi), following an intracellular acid load in myocytes loaded with carboxy-SNARF-1 (a pH-sensitive fluorescent dye, used to measure pHi)). In other experiments, in-vitro CA activity was assessed from the time-course of pH change after addition of CO2-saturated water to a buffered solution containing either CA II or a cardiac homogenate. In further experiments, intracellular CA activity was assessed from the rate of CO2-induced fall of pHi. Three major results emerged, (i) In intact myocytes, CA activity doubles acid extrusion on sarcolemmal NBC, but has no effect on NHE activity. Facilitation of NBC activity by CA is likely to be mediated by an intracellular CA isoform. (ii) In-vitro and intracellular CA activity displays strong pH-dependence within the physiological pH range, activity declining with a fall of pH. (iii) The NHE inhibitor, cariporide, the bicarbonate transport inhibitors DIDS (4,4'- diisothiocyanatostilbene-2,2'-disulphonic acid) and S0859 (an experimental compound from Sanofi-Aventis), and the aquaporin blocker, pCMBS (p-chloromercuribenzene sulphonate), all showed strong inhibitory activity towards CA in-vitro, but had no effect on intracellular CA activity. Overall, the work provides the first clear demonstration of a functional role of CA activity in H+-equivalent transport in a wild-type cell. CA thus represents an important regulatory mechanism of H+ -equivalent transport. The pH sensitivity displayed by in-vitro and intracellular CA activity may also have significant functional consequences for pHi regulation. CA inhibition by various membrane transport inhibitors highlights the need for careful drug and experimental design, to avoid secondary inhibition of CA activity and its side-effects. The present work thus provides insight into the functional roles of CA, plus important new information on the enzyme's pharmacological properties.